Revisiting the Meaning of Jihad: A Critical Analysis of Istishhād Hadiths through the Perspective of Ma‘āni al-Ḥadīth - Zulfarizal Zulfarizal; Muhammad Abdul Kharis; Muhammad Waris Ali (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2026)
This study aims to correct the distorted understanding of the concept of jihad having often been misinterpreted textually by radical groups legitimizing violence through hadiths of istishhād (reports concerning martyrdom through suicide operations). Using the Ma’āni al-Ḥadīth approach, this research explores the semantic and linguistic structure of the hadiths, their historical context (asbāb al-wurūd), and their contemporary social relevance. The study employs a qualitative library research method, supported by interviews with two former terrorism convicts, Ali Imron and Khairul Ghazali, to reveal the ideological framework behind radical interpretations of jihad and istishhād. The findings reveal that the distortion of jihad stems from a rigid textual-literal approach neglecting the objectives of Islamic law (maqāṣid al-syarī’ah) and the socio-historical context of the prophetic traditions. In fact, jihad in the hadith perspective extends beyond physical warfare (qitāl) to encompass moral, social, and humanitarian struggles promoting justice and peace. Using the Ma’āni al-Ḥadīth approach, this research underlines the need for a comprehensive reconstruction of jihad interpretation, the one avoiding extremist readings and restoring its true essence as an ethical struggle for the well-being of humanity.